Oxidized biochar obtained from rice straw as adsorbent to remove uranium (VI) from aqueous solutions. Issue 2 (April 2021) - Ahmed, Waqas; Mehmood, Sajid; Qaswar, Muhammad; Ali, Sehrish; Khan, Zulqarnain Haider; Ying, Huang; Chen, Di-Yun; Núñez-Delgado, Avelino
Abstract: In this study, rice straw derived biochar (RSBC) was used as a precursor for obtaining oxidized biochar (RSBC-Ox), for which the capability for adsorbing/removing uranium (VI) from aqueous solutions was investigated. The U(VI) removal efficacy of RSBC-Ox was tested for different values of pH, ionic strength, initial concentration of U(VI) and temperature. RSBC-Ox reached 242.65 mg g −1 as the most effective score regarding uptake. Experimental adsorption data fitted well to a pseudo-second-order kinetic model (reaching a value at equilibrium of qe = 148.9 mg g −1, R 2 = 0.99), and to the Langmuir isotherm (achieving a maximum score of qmax = 242.65 mg g −1, R 2 = 0.99). Thermodynamics revealed that adsorption was endothermic, and indicated inner-sphere complexation, and entropy-driven with a relatively increased randomness in the solid-solution interface. This research could be of aid for reusing rice straw as an effective and low-cost adsorbent for U(VI) removal in various environmental conditions, simultaneously promoting resource utilization and sustainable management of the materials, aiding to protect the environment and human health. Graphical Abstract: ga1 Highlights: U(VI) removal by oxidized biochar from rice straw (RSBC-Ox). Pseudo-second order model and Freundlich isotherm model fitted well the experimental data. Thermodynamics revealed that U(VI) adsorption was endothermic, primarily governed by the surface complexation mechanism. Application of RSBC-Ox in real wastewater gave promising U(VI) removal results.